2011
DOI: 10.1177/0333102411413162
|View full text |Cite
|
Sign up to set email alerts
|

Changes in headache frequency in premenopausal obese women with migraine after bariatric surgery: A case series

Abstract: Among migraine-suffering premenopausal obese women, we found a reduced frequency of migraine attacks and improvement of headache-related disability post bariatric surgery. Our findings should be interpreted cautiously. The absence of a control group and the non-blinded nature of our small study make it difficult to draw firm conclusions about the causal nature of the headache changes observed in this population. Further study is needed to evaluate the possible specific effects of surgical weight loss on migrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 23 publications
3
51
0
Order By: Relevance
“…Four studies described a surgical approach: two were procedures for deactivation of trigger sites [9,10], one approach was the occipital nerve stimulation [11], and one approach was bariatric surgery for obese patients patients comorbid migraine [12]. Two studies reported short-term longitudinal observations of patients currently under treatment for migraine who were prescribed tailored medications including both acute and prophylactic ones [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies described a surgical approach: two were procedures for deactivation of trigger sites [9,10], one approach was the occipital nerve stimulation [11], and one approach was bariatric surgery for obese patients patients comorbid migraine [12]. Two studies reported short-term longitudinal observations of patients currently under treatment for migraine who were prescribed tailored medications including both acute and prophylactic ones [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen from 60 phase 2 studies scored over 65% and were included for further analysis (Table 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Pain had been measured and recorded in over 2000 subjects in randomized controlled trials (RCT, n=7) or observational studies (n=9).…”
Section: Resultsmentioning
confidence: 99%
“…Peterline et al survey, also showed higher prevalence of migraine (OR = 1.39) among women with obesity in comparison with normal-weight and healthy women (36). Vo M et al showed that morbid obese women had an almost 1.48-fold elevated risk of migraine headache in comparison with normal weight women, and also women with morbid obesity (OR¼2.07; 95% CI 1.27 -3.39) had the greatest chance of migraines (20).…”
Section: The Association Between Morbid Obesity and Migraine Headachementioning
confidence: 99%
“…Particularly in patients suffer from morbid obesity that has higher frequency of migraine headache. Recently, it has been showed that surgical weight loss with bariatric surgery can improve migraine headache in morbidly obese patients (19,20).…”
Section: Introductionmentioning
confidence: 99%